Perception of the sul-mineira population about the rabbit meat consumption and nutritional benefits (Research, Society and Development, 2021)
Rabbit meat has a low-fat content, higher protein content than beef and pork. In addition, rabbit meat has high rates of omega 3, B vitamins and minerals such as potassium, iron, phosphorus and calcium. However, this meat is not widely known and consumed in Brazil. Therefore, this study aimed to analyze the consumer profile perception about rabbit meat in southern Minas Gerais (Brazil) and the main reasons for approval or disapproval. A virtual form was applied and 309 answers were obtained from residents of 44 cities in Minas Gerais. From the analysis was possible to define four consumer profiles: I) never consumed; II) wants to consume; III) have already consumed once or twice a year; and IV) have already consumed more than twice a year. Majority of the interviewees were profile I and minority were profile IV, which is also characterized by consumers who know about rabbit meat nutritional benefits. The results indicated resistance by most people in relation to the rabbit meat consumption, probably this is due the cultural reasons. These results contribute to the development of productive strategies, helping to increase the consumption of this food.